Keberlanjutan Kelembagaan Sistem Integrasi Tanaman Padi-Ternak Sapi: Studi Kasus pada Kelompok Tani Terang-Terang - Lira, Jumiati; Purwanto, Moh. Yanuar Jarwadi; Yani, Moh.; Molla, Saleh; Akbar, Akbar (Hasanuddin University, 2024)
The objectives of this paper are 1. Identifying the integrated farming system 2. Interconnection of Resources (R), Organization (O), and Norms (N) in supporting the sustainability of crop-livestock integration activities; and 3. Knowing the implementation of institutional sustainability strategies in the Terang-terang Farmers Group. This research is qualitative research with a case study approach to the Terang-terang Farmer Group in Popo Village, South Galesong District, Takalar Regency, South Sulawesi Province using a qualitative descriptive analysis method. The integrated farming system managed by the Terang-terang Farmer group by processing livestock waste into biogas and bio-slurry is utilized as household input and rice plants. Plant waste in the form of straw is used as green and processed animal feed; 2. Resources (R) managed in the form of human resources as many as 25 people, a land area of 13.5 hectares, a total of 55 cattle, a biogas reactor with a capacity of 6 tons, agricultural machinery, namely planting tools, tractors, harvesting machines. There is an organizational structure and there is a division of tasks between individuals working, the norms applied are unwritten rules because there are no written rules. The division of tasks is based on beliefs and customs, no written sanctions are given if there are violations in the group; and 3. The sustainability framework of the Terang-terang Farmer Group is based on reflective strategies and can still be developed with interactive strategies. The integrated agricultural system managed by the Terang-Terang Farmers Group is by processing cattle waste into biogas and solid and liquid bioslurry which is then used as household input and rice plants, plant waste in the form of straw is used as green animal feed, and processed feed; 2. Resources (R) managed in the form of human resources of 25 people, land area of 13.5 hectares, number of cattle of 55 heads, biogas reactor with a capacity of 6 tons, agricultural machinery namely planting tools, tractors, harvesting machines and other equipment are available. quite supportive of integration activities. There is an organizational structure and there is a division of tasks between each individual in the work, the norms that are applied are still unwritten rules and there are no written rules yet. The division of tasks is based on beliefs and customs, no written sanctions have been given if there are violations in the group, the system for sharing results has not been written; and 3. The sustainability framework of the Terang-Terang Farmers Group is based on a reflective strategy and can still be developed using an interactive strategy.